Honouring COVID-19 restrictions: A qualitative study of the virtual asd diagnostic pathway in a uk nhs camhs service. (13th April 2021) - Ecob, C.; Olety, S.; Lancaster, R.; Harris, A.
Abstract : Introduction: The Multi-Agency Autism Team (MAAT) diagnose Autism Spectrum Disorder (ASD) in children and young people using a multi-stage assessment process. In March 2020, the UK went into lockdown due to the COVID-19 pandemic, affecting the MAAT's ability to continue their typical diagnostic pathway. Objectives: This qualitative study aimed to assess the effectiveness and feasibility of a virtual ASD diagnostic pathway. Methods: From March – September; one hundred detailed developmental history assessments were conducted over the telephone, fifteen socially-distanced BOSA (Brief Observation of Symptoms of Autism) assessments were piloted, twenty-five multi-disciplinary formulation meeting were held over a video platform, and sixty diagnosis feedback consultations were conducted via telephone or video call. Structured interviews were conducted with clinicians and service-users. Results: revealed that telephone developmental history assessments were generally preferable over face-to-face appointments, and video-based formulation meetings were effective, productive and resulted in higher clinician attendance. The qualitative data on feedback appointments was mixed. Clinicians felt that telephone appointments were less personable and ethical; whereas, video-based feedback appointments allowed for more empathy. However, the majority of service-users opted for tele-calls over video-calls for these appointments. Socially-distanced BOSAs obtained positive clinician feedback in general. Service-user feedback was mixed; some found the experience uncomfortable and unfamiliar, whilst others enjoyed the experience. Overall, service-users were content with the knowledge that it may support a diagnostic outcome for their child. Conclusions: We concluded that the overall experience of the virtual ASD diagnostic pathway was a positive and informative process, identifying opportunities for permanent change to the service.